Associations of delay discounting and drinking trajectories from ages 14 to 22. (17th March 2022) - Fröhner, Juliane H.; Ripke, Stephan; Jurk, Sarah; Li, Shu‐Chen; Banaschewski, Tobias; Bokde, Arun L.W.; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Heinz, Andreas; et al.
Abstract: Background: While drinking alcohol, one must choose between the immediate rewarding effects and the delayed reward of a healthier lifestyle. Individuals differ in their devaluation of a delayed reward based on the time required to receive it, i.e., delay discounting (DD). Previous studies have shown that adolescents discount more steeply than adults and that steeper DD is associated with heavier alcohol use in both groups. Methods: In a large‐scale longitudinal study, we investigated whether higher rates of DD are an antecedent or a consequence of alcohol use during adolescent development. As part of the IMAGEN project, 2220 adolescents completed the Monetary Choice Questionnaire as a DD measure, the Alcohol Use Disorders Identification Test, and the Timeline Follow Back interview at ages 14, 16, 18, and 22. Bivariate latent growth curve models were applied to investigate the relationship between DD and drinking. To explore the consequences of drinking, we computed the cumulative alcohol consumption and correlated it with the development of discounting. A subsample of 221 participants completed an intertemporal choice task (iTeCh) during functional magnetic resonance imaging at ages 14, 16, and 18. Repeated‐measures ANOVA was used to differentiate between high‐risk and low‐risk drinkers on the development of neural processing during intertemporal choices. Results: Overall, high rates of DD at age 14 predicted a greater increase in drinking over 8 years. In contrast, on average, moderate alcohol use did not affect DD from ages 14 to 22. Of note, we found indicators for less brain activity in top‐down control areas during intertemporal choices in the participants who drank more. Conclusions: Steep DD was shown to be a predictor rather than a consequence of alcohol use in low‐level drinking adolescents. Important considerations for future longitudinal studies are the sampling strategies to be used and the reliability of the assessments. Abstract : In a longitudinal study, we investigated adolescents from age 14 to 22 to clarify whether drinking is a cause or a consequence of delay discounting (DD), both measured by questionnaires. A subsample completed a DD task during fMRI. Steeper DD at age 14 was associated with higher increase of drinking. Decision‐related signal in medial frontal gyrus (MFG) was higher in those who drank less initially, and insula signal was higher in those who showed less increase of drinking.